Inside Cover: Selective Protein Hyperpolarization in Cell Lysates Using Targeted Dynamic Nuclear Polarization (Angew. Chem. Int. Ed. 36/2016). Issue 36 (14th July 2016) - Viennet, Thibault; Viegas, Aldino; Kuepper, Arne; Arens, Sabine; Gelev, Vladimir; Petrov, Ognyan; Grossmann, Tom N.; Heise, Henrike; Etzkorn, Manuel
Abstract : Directing hyperpolarization to a target protein makes it possible to selectively filter out signals of specific proteins from a large background. In their Communication onpage 10746 ff., M. Etzkorn et al. show that dynamic nuclear polarization can be directed to a target protein by using a biradical‐labeled ligand. The resulting reduction of the background facilitates solid‐state NMR studies of the target protein in increasingly native environments.